What does it mean to construct an argument in academic writing? A synthesis of English for general academic purposes and English for specific academic perspectives - Yasuda, Sachiko (Journal of English for academic purposes, 2023)
Argumentation is a crucial skill in higher education, and argumentative essays are common genres that students have to write. However, studies have shown that many L2 learners have difficulty in developing an argument in their essays (Wingate, 2012) and that teachers face challenges in gaining an understanding of argumentation and how to scaffold L2 learners (Kibler, 2017). As a first step toward establishing a comprehensive argumentative writing framework for learners and teachers, this article presents a synthesis of relevant empirical studies that illuminate the argumentative features of academic discourse. Focusing on two research perspectives—argumentative writing for general academic purposes and argumentative writing for specific academic purposes—, this review aims to establish a nexus between generic knowledge about argumentation and discipline-specific contexts for argumentation. This review forms the theoretical foundations for the improvement of English for academic purposes practice, providing choices that teachers may have been previously unaware of, thus empowering them to move beyond the constraints of a structure-oriented understanding of argumentative writing and helping learners navigate the demands of higher education. •This article provides a conceptual review of empirical studies on argumentative writing.•The article establishes a nexus between generic knowledge about argumentation and discipline-specific argumentation.•The EGAP perspective highlights cognitive and linguistic skills involved in argumentative writing.•The ESAP perspective manifests the complex intersection of multiple social factors involved in argumentative writing.•This review concludes with a perspective on writers' agentive meaning-making choices in argumentation.